Simulation Research on Active Noise Reduction in Driver’s Cab ofAutonomous-rail Rapid Tram - ZHOU Sheng; HUANG Wanjun; LI Wei; XIAO Lei; HUANG Jin; HE Jie (Kongzhi Yu Xinxi Jishu)
Noise of autonomous-rail rapid tram mainly comes from giant mechanical and electrical equipment installed on the chassis of cab. The noise has a wide frequency band and obvious time-varying characteristics. Traditional noise reduction technology can only work in specific frequencies and working conditions, and may not fully meet the noise reduction requirements of the autonomous-rail rapid tram. In order to further improve the comfort of driving environment for autonomous-rail rapid tram cab, this paper studies the active noise reduction technology of autonomous-rail rapid tram cab. A wideband feedforward active noise reduction method is proposed, which adopts FxLMS control algorithm, and the control algorithm is derived, and the noise data of autonomous-rail rapid tram is used in the Matlab/Simulink platform for modeling and simulation. The results show that the active noise reduction technology can effectively reduce noise level in cab and the noise reduction is about 20 dB.